Impacts of Ecology, Parasite Antigenic Variation, and Human Genetics on RTS,S/AS01e Malaria Vaccine Efficacy - Bell, Griffin J. (Curr Epidemiol Rep, 2021)
PURPOSE OF REVIEW: Global malaria elimination has little chance of success without an effective vaccine. The first malaria vaccine, RTS,S/AS01e, demonstrated moderate efficacy against clinical malaria in phase III trials and is undergoing large-scale effectiveness trials in Africa. Importantly, the vaccine did not perform equally well between phase III study sites. Though reasons for the moderate efficacy and this variation are unclear, various mechanisms have been suggested. This review summarizes the recent literature on such mechanisms, with a focus on those involving landscape ecology, parasite antigenic variation, and human host genetic differences. RECENT FINDINGS: Transmission intensity may have a role pre- and post-vaccination in modulating immune responses to the vaccine. Furthermore, malaria incidence may “rebound” in vaccinated populations living in high transmission intensity settings. There is growing evidence that both genetic variation in the parasite circumsporozoite protein and variation of human host genetic factors affect RTS,S vaccine efficacy. These genetic factors may be interacting in complex ways to produce variation in the natural and vaccine-induced immune responses that protect against malaria. SUMMARY: Due to the modest efficacy of RTS,S/AS01e, the combinations of factors (ecological, parasite, human host) impacting its effectiveness must be clearly understood, as this information will be critical for implementation policy and future vaccine designs.